'COVID-Somnia' in healthcare workers during the pandemic. Issue 4 (8th August 2022) - Özçelik, Neslihan; Kesin, Hasan Veysel; Telatar, Gokhan; Özyurt, Songül; Yılmaz Kara, Bilge; Gümüş, Aziz; Hocaoğlu, Çiçek; Şahin, Ünal
ABSTRACT: Objectives: Sleep disorders associated with COVID-19 pandemic are termed as 'COVID-somnia.' In this study, we sought to assess the prevalence of COVID-somnia in healthcare workers, establish the factors that trigger this condition, and to investigate its relationship with anxiety and depression symptoms. Methods: This cross-sectional study was conducted between April 2021 and June 2021, and it included healthcare workers who served during the pandemic. Participants' demographic data, Beck Depression and Anxiety Inventories, Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), and Insomnia Severity Index (ISI) were used, and the results were statistically analyzed. Multiple analyses of factors affecting ESS and ISI scores were evaluated using binary logistic regression model and PSQI score were analyzed using a multiple linear regression model. Results: A total of 1, 111 healthcare workers who served during the pandemic voluntarily enrolled to the study. The mean age was 37.3 ± 8.48 years, and 63.5% were females. Our study showed that the healthcare workers, evaluated with the PSQI, experienced a deterioration of sleep quality. Primary factors affecting this are working on the front line, the presence of chronic diseases, depression, and anxiety. Regression analyses identified depression and anxiety as the common factors affecting ESS, ISI, and PSQI scores. Conclusion: Raising awareness regarding COVID-somnia among healthcare workers, who play a leading role in curbing the pandemic, would reduce sleep disturbances, depression, and anxiety. It would also contribute to the planning and implementation of preventive and therapeutic mental health programs with a multidisciplinary approach.